Innovations in Medical Education in Gastrointestinal Surgery Using Interactive Anatomical Tables - A. D. Kashtanov; E. O. Stetsyk; S. S. Dydykin; O. V. Kytko; E. M. Trunin; O. Yu. Aleshkina; A. N. Lavrentieva; A. N. Andreeva; D. S. Alekseeva; A. A. Muratova; A. Yu. Kharina; V. V. Tatarkin; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
The introduction of digital technologies into the learning process for medical university students represents a new paradigm in medical education since high level of criteria for assessing the quality of learning of a medical student require the application of modern technologies in training fundamental disciplines and, in particular, anatomy. Thanks to virtual technologies, conditions are created for modeling and integrating the student into conditions close to real ones, which increases the interest and involvement of students in the educational process and, as a result, a subjective improvement in the process of assimilation of the material. Traditional education based on dissection materials cannot fully provide for the massive training of students, as biological materials cannot be restored or preserved and are quickly damaged. 3D models are devoid of these limitations.Aim: to evaluate the effectiveness of digital dissection in the educational trajectory of clinical anatomy using interactive anatomical tables and the need of students for the active use of these aids.Materials and methods. Four groups of students were formed: three groups were studying the material using various anatomical tables and one group used the traditional method. To control the effectiveness of the educational process, before the start of training, entrance testing was conducted in all groups. At the end of classes on individual topics, participants completed exit testing, as well as a questionnaire.Results. The analysis of learning outcomes shows a significantly higher level of absorption of the material among students in groups where 3D anatomical models were used during classes. This indicates that students’ subjective experience of the learning process has improved due to their increased involvement in the class and their interest in innovative teaching methods.Conclusion. We plan to study learning outcomes in more detail to identify any differences in the formation of general and professional competencies among students. This information will help us make informed decisions about the widespread use of anatomical models in educational practice.